Genetic Similarity of two different color Local Guinea Fowl (Numida Meleagris) By Using RAPD-PCR Technique - Hurea S. Abdulrazaq (Zanco Journal of Pure and Applied Sciences, 2020)
The aim of present study to determine DNA polymorphism, between and within two different color (white) and (black) guinea fowl lines. Blood samples were collected about 3 ml of 30 white guinea fowl and 30 black guinea fowl, in six different local farms. DNA was isolated, the purity of the DNA samples ranged from 1.8 to 1.9. RAPD – PCR was used to evaluate genetic similarity between the lines of guinea fowl. Using eighteen primers for amplification of RAPD, from Gen Script USA. A total of (14) primers out of (18) primers gave results to find Genomic DNA complementary sites. After electrophoresis the largest number of bands were appeared with OPA-03 primers, but the smallest was obtained when OPQ-15 primer used. Determined Genetic similarity as the mean for the primers used, between the black and white guinea fowl, was 0.76. The coefficient of genetic similarity within white guinea fowl line, was 0.78 and 0.73 within black guinea fowl line.